Analisis Yuridis Penggunaan Mediator Non-Sertifikasi dalam Proses Mediasi Perkara Perdata di Pengadilan Negeri Sumedang - Hilda Emillia; Yasfi Lubnatul Aulia; Sofi Nurmala; Nur Aulia Husaeni; Samsul Bahri (LEX FAMILIA: Journal of Islamic Family Law, 2026)
Mediation is a mandatory procedure in resolving civil cases at the court of first instance as regulated in Supreme Court Regulation (PERMA) Number 1 of 2016. The regulation requires mediators to possess a mediator certificate; however, in practice, many courts face a shortage of certified mediators, leading to the use of non-certified mediators. This study aims to analyze the legal basis and mechanisms for utilizing non-certified mediators, examine the juridical implications on the validity of the mediation process and court decisions, and identify obstacles and legal solutions at the Sumedang District Court. The research employs an empirical juridical method with a descriptive analytical approach. Primary data were obtained through interviews and observations at the Sumedang District Court, while secondary data were gathered through literature review. The findings reveal that the use of non-certified mediators holds legal legitimacy under Article 13 paragraph (2) of PERMA Number 1 of 2016, which permits non-certified judges to serve as mediators based on a decree issued by the chief justice of the court. Formally, the mediation process and resulting decisions remain legally valid; however, substantively, the quality of mediation is lower due to limited mediator skills, rendering mediation merely a procedural formality. Identified obstacles include insufficient mediator competence, limited time of judges serving dual roles as mediators, lack of good faith from the parties, inadequate mediation facilities, and unsupportive legal culture. Recommended solutions encompass expanding mediator certification programs, empowering certified non-judge mediators, improving facilities, and disseminating the benefits of mediation to the public.